Human Resource Antecedents and Generation Y’s Job Motivation: A Case Study on Malaysian SMEs - Pui, Chien Ying (2014)
With the on-going war for talent and the retirement of the Baby Boomers, there is an increasing interest shown towards the newest entrant to the workplace; the Generation Ys (Gen Ys). Gen Ys are said to differ significantly from previous generations and have distinct characteristics, expectations and motivational needs. It has been reported that Gen Ys have high expectations and favour working for large organisations over Small and Medium Enterprises (SMEs). Existing Human Resource (HR) practices do not seem to work well on Gen Ys. Thus, it has become a challenge for Malaysian SMEs to manage/motivate the Gen Ys effectively. The aim of this study is to examine the HR Antecedents that influence Gen Ys’ job motivation in Malaysian SMEs. The HR Antecedents encompasses Staffing and Recruitment, Training and Development, Rewards and Recognition and Retaining practices. The motivating factors include parent’s approval/input, peers/friends’ recommendations, opportunities to gain new experiences, opportunities to travel abroad, opportunities to volunteer/contribute to society, the availability of up-to-date technology, continuous training and development of new skills, opportunities for further education, career growth opportunities, clear guidance from supervisors via coaching/mentoring, regular feedback on performance, teamwork, financial rewards, non-financial rewards, instant rewards, constant recognition, rapid promotions, bring trusted with increased responsibilities, pay-for-performance, open and honest communication, freedom, flexibility, work-life-balance, challenging/meaningful work and a fun/casual work environment. This study found that Training and Development, Rewards and Recognition and Retaining practices have a significant impact on Gen Ys’ job motivation in Malaysian SMEs. However, not all the Staffing and Recruitment antecedents were important to them. Overall, there appears to be a big gap between the Gen Ys’ expectations and current SMEs’ HR Practices. Thus, managers are advised to adjust their HR policies to better manage/motivate the Gen Ys in order to boost performance. This can be done by providing Gen Ys with up-to-date technology, incorporating digital training, leveraging on flatter hierarchy, widening span of control, decentralisation, promoting teamwork and mentor-mentee assignments, cafeteria benefits and keeping in tune with Corporate Social Responsibility (CSR) policies.